New Paradigm of Restorative Justice Based on the Perspective of Customary Law in Law No. 1 Year 2023 on the Criminal Code - Muhammad Fahlebvy; Muklis Al'anam; Dwi Rahman Suhada (Vonis, 2025)
The paradigm shift in the modern criminal justice system shows an increasing interest in the restorative justice approach as an alternative to resolving criminal cases. This article aims to analys the relevance of restorative justice principles rooted in the customary law perspective in Indonesia as a basis for the implementation of law the new criminal code. Through library research, this study uses a normative method that examines legal norms on restorative justice in relation to customary law that can strengthen restorative justice. The implications of this study are expected to contribute to the development of criminal law policies that accomodate customary values as part of achieving substantial justice.